Smartphone Addiction of Students: A Scale Development in the Context of Undergraduate Students in Bangkok - Chanadda Petchprayoon, ชนัดดา เพ็ชรประยูร; Numchai Supparerkchaisakul, นำชัย ศุภฤกษ์ชัยสกุล; ภัทราวิวัฒน์, กาญจนา (Dusit Thani College Journal, 2018)
The objective of this research was to develop a smartphone addiction scale. The sample consisted of 986 undergraduate students in Bangkok. The data was collected by using 30 item Smartphone addiction scale. Smartphone addiction scale was considered for its content validity by academic experts and its reliability was 0.94. The results of second order confirmatory factor analysis showed that smartphone addiction had 6 factors; salience, mood modification, loss of control, withdrawal, conflict, and relapse, resulting in a 24-items scale. The convergent validity and construct reliability of this scale were accepted. The average variance extracted was ranged 0.52 - 0.79 and the construct reliability was ranged 0.79 - 0.93.